Upaya Meningkatkan Kemampuan Passing Bawah Bola Voli Melalui Media Dinding Sekolah dengan Metode Drill Pada Siswa Kelas IV SD Negeri Salem 02 - Dira Anggara; Dedi Iskandar (Universitas Palan, 2024)
This research aims to improve students' bottom passing skills using school wall media using the Drill method. This research is Classroom Action Research which was carried out in 2 cycles. The research was carried out in April of the 2023/2024 academic year. Researchers collaborate with teachers and colleagues. This research procedure refers to the Kemmis & Mc model. Taggart which includes planning, implementing actions, observing and reflecting. The research subjects were fourth grade students at SD Negeri Salem 02, totaling 20 students, 9 male students and 11 female students. The instruments used are teacher activity observation assessment sheets, student activity observation sheets, and performance assessment sheets. The results of the research showed that there was an increase in cooperation in the first cycle, namely students' bottom passing skills using school wall media. Of the 20 students at meeting 1, there were 10 students (50%) who had entered the criteria for completion, while at meeting 2 there were 12 students (60%) who had entered. in the complete criteria. In cycle II, students' underpassing skills used school wall media. Of the 20 students at meeting 1, 15 students (75%) had entered the completion criteria, while at meeting 2 there were 18 students (90%) had entered the completion criteria. Based on these data, it can be concluded that the use of the Drill method with school walls can improve students' bottom passing skills in class IV of SD Negeri Salem 02, Salem District, Brebes Regency.